Identification and Ranking of Digital Social Responsibility Dimensions in Virtual Networks with Emphasis on Instagram - Aflouk Al-Shafee, Karar Ali; Davazdahemami, Hamid; BDAIWI OBAID ALSHAMMARI, HATEM; Sharifi , Saeid (Business, Marketing, and Finance Open, 2024)
This study aimed to identify and rank the dimensions of digital social responsibility in virtual networks, with an emphasis on Instagram. The statistical population in the qualitative phase included all experts related to the research topic, and interviews continued until theoretical saturation was achieved. Simultaneously with the interviews, data analysis was conducted using content analysis, including open, axial, and selective coding, validated through ATLAS.ti 8 software. In the quantitative phase, data were analyzed using SPSS and AMOS software. The analytical process included the calculation of statistical indices such as mean, standard deviation, Kendall’s coefficient of concordance, and exploratory and confirmatory factor analysis. These analyses were conducted to assess the validity and reliability of the questionnaire and the research model. In the data analysis, 261 initial concept codes, 8 main concept codes, and 31 sub-concept codes were identified to explain the primary concepts. The quantitative findings indicated that all dimensions of digital social responsibility in virtual networks, with an emphasis on Instagram, were significant at the 0.01 level. This means that the effect of each dimension of digital social responsibility in virtual networks, focusing on Instagram, was greater than the hypothetical mean of 3, and this difference was statistically significant. Furthermore, the ranking of the dimensions revealed that each component was evaluated relative to others based on its average ranking. Components with higher average rankings were considered more important. A significance level of less than 0.05 indicated that the observed differences in rankings were statistically significant. Based on the research findings, the results demonstrated that all dimensions of digital social responsibility on Instagram were assessed above the average level and held special importance for users. These differences were not only significant but also indicated that Instagram users paid considerable attention to these dimensions and expected the platform to adhere to higher standards in these areas. The ranking results showed that the various dimensions of digital social responsibility in virtual networks, with an emphasis on Instagram, were valued differently by users, with significant differences in their prioritization.